20-HETE is Associated with Unfavorable Outcomes in Subarachnoid Hemorrhage Patients. Issue 9 (September 2015) - Donnelly, Mark K; Crago, Elizabeth A; Conley, Yvette P; Balzer, Jeffery R; Ren, Dianxu; Ducruet, Andrew F; Kochanek, Patrick M; Sherwood, Paula R; Poloyac, Samuel M
Emerging evidence has suggested that patients experiencing aneurysmal subarachnoid hemorrhage (aSAH) develop vascular dysregulation as a potential contributor to poor outcomes. Preclinical studies have implicated the novel microvascular constrictor, 20-hydroxyeicosatetraenoic acid (20-HETE) in aSAH pathogenesis, yet the translational relevance of 20-HETE in patients with aSAH is largely unknown. The goal of this research was to determine the relationship between 20-HETE cerebrospinal fluid (CSF) levels, gene variants in 20-HETE synthesis, and acute/long-term aSAH outcomes. In all, 363 adult patients (age 18 to 75) with aSAH were prospectively recruited from the University of Pittsburgh Medical Center neurovascular Intensive Care Unit. Patients were genotyped for polymorphic variants and cytochrome P450 (CYP)-eicosanoid CSF levels were measured over 14 days. Outcomes included delayed cerebral ischemia (DCI), clinical neurologic deterioration (CND), and modified Rankin Scores (MRS) at 3 and 12 months. Patients with CND and unfavorable 3-month MRS had 2.2- and 2.7-fold higher mean 20-HETE CSF levels, respectively. Patients in high/moderate 20-HETE trajectory groups (35.7%) were 2.5-, 2.1-, 3.1-, 3.3-, and 2.1-fold more likely to have unfavorable MRS at 3 months, unfavorable MRS at 12 months, mortality at 3 months, mortality at 12 months, and CND, respectively. These results showed that 20-HETE is associated with acute and long-term outcomes and suggest that 20-HETE may be a novel target in aSAH.